Effectiveness of Clavicula Pro Humero Reconstruction for Elderly Patients: Report of Two Cases. (25th October 2016) - Okimatsu, Sho; Kamoda, Hiroto; Yonemoto, Tsukasa; Iwata, Shintaro; Ishii, Takeshi
Abstract : Clavicula pro humero (CPH) reconstruction is a method that is used after proximal humeral excision. During CPH reconstruction, the ipsilateral clavicle is rotated downward and connected to the preserved distal humerus by using plates and screws. This method is frequently used for reconstruction surgeries involving young patients and has positive outcomes. In this study, we describe two cases of CPH reconstruction that were performed on elderly individuals after wide resection of the proximal humerus; postoperative results from these surgeries were satisfactory. The average Musculoskeletal Tumor Society (MSTS) functional score after surgery was 68.5%, indicating that CPH reconstruction is suitable for not only younger but also elderly patients, particularly those over the age of 65 years.